“Effectiveness Of Benson’s Relaxation Therapy On Reduction Of Pain And Stress Among Post L.S.C.S Primigravida Mothers ” (Journal of Pharmaceutical Negative Results, 2022)
Background: Pregnancy and Childbirth are normal life events for all women but sometimes it creates pain and stress related to delivery and its most common in primigravida mothers with C – Section procedure. In 2021 birth rate is 17.1 % per 1000 population in India. Where according to 5th NFHS the national c-section rate is 21.5 higher than the ideal percent 10 -15 % in India. Now a days the trend of delivery by c – section is increased sometimes its necessary (big baby, contracted pelvic, prolong labor) to do c -section and sometime c- section do due to mother is not want vaginal delivery due to fear, lack of cooperativeness etc. Due to c – section mother feels stress, pain, disability due to operative trauma. For that painkillers, antibiotics (pharmacological) are necessary to give but with medicine also some therapies (non-pharmacological) are necessary to reduce pain, stress, anxiety etc. non – pharmacological methods are cheap, suitable and no need of any specific training. Aims : The main aim of this study is to assess the effectiveness of non-pharmacological management especially Benson’s relaxation therapy for pain and stress that occur due operative trauma among post LSCS women.Objective : To assess the pre-test and post-test level of pain and stress among post LSCS mothers in experimental and control group before Benson’s relaxation therapy. To assess the effectiveness of Benson’s relaxation therapy by comparing the pre-test and post-test level of pain and stress among post LSCS mothers in experimental and control group.To find out the association between the post intervention pain and stress among post LSCS mothers with their selected demographic variables in both experimental and control group. Methodology: Quasi experimental design with pretest – posttest only control group design was used by the researcher. 60 post-natal mothers were selected as a sample from those 30 mothers selected for experimental group and 30 selected for control group. samples were selected from Dr. N. D. Desai College and Hospital from Nadiad City. Samples was selected by Non-Probability Purposive Sampling Technique. Data were analyzed by using SPSS software and frequency and percentage, tables, graph etc. were used to represent the statistical data. Results: Majority of women underwent C – section were primigravida mothers. For pain, in experimental group, Mean Difference of pre test and post test is 3.24 (32.4%) and calculated “t” value is 29.512 which is more than tabulated value 2.045. In control group, Mean Difference of pretest and posttest is 0.30 and calculated “t” value is 2.208. So, after administration of BRT pain score is reduced in experimental group than the control group. For stress, in experimental group, Mean Difference of pretest and posttest is 4.71 (11.77%) and calculated “t” value is 25.791 which is more than tabulated value 2.045. In control group, Mean Difference of pretest and posttest is 0.17 and calculated “t” value is 0.376. So, result reveals that on 3rd day after administrating BRT, stress were reduced in experimental group than the control group.Conclusion: The result of present study shows that Benson’s relaxation therapy has positive impact on reduction in pain and stress among post LSCS primigravida mothers in hospital where as in control group routine care is not much more effective to reduce pain.